Respuesta :
Answer:
Both are correct because after substituting the same value into both expressions, the result is the same.
Step-by-step explanation:
Given the expression:
(1/6)*(6*x + 12) - (1/2)*(4*x + 2)
Applying distributive property:
(1/6)*6*x + (1/6)*12 - (1/2)*4*x - (1/2)*2 =
= x + 2 - 2x - 1 =
= -x + 1
Then, for any number substituted into both equations, the result is the same
Answer:
c: Both are correct because after substituting the same value into both expressions, the result is the same.
Step-by-step explanation:
did it on edge 2020